A CROSS-SECTIONAL STUDY ON COMPARISON OF THE LEFT AND RIGHT SIDES OF PATELLA: ANATOMIC DIFFERENCES. - Vivekanand; Kumari Rashmi; Birendra Kumar Sinha (Student’s Journal of Health Research Africa, 2024)
Background The patella, or kneecap, is a crucial component of the knee joint, significantly influencing its biomechanics and functionality. Anatomical variations in patellar dimensions are important for orthopedic surgery, rehabilitation, and the diagnosis of knee disorders. Despite the extensive literature on patellar anatomy, there is limited research comparing the anatomic differences between left and right patellae. This study aims to investigate and compare the anatomic differences in patellar dimensions between the left and right sides to determine any significant asymmetries that may impact clinical practices. Methods A comparative cross-sectional study was carried out using 40 dry patellae (21 right-sided and 19 left-sided). Patellae were classified based on Koyuncu’s morphological classification. Key parameters measured included patella height, width, thickness, and the dimensions of the medial and lateral articular facets. Digital vernier calipers were used for precise measurements. Statistical analysis was performed using SPSS. Results The mean values for all measured parameters were slightly higher for the left patellae compared to the right. However, the differences were not statistically significant (p > 0.05). For example, the mean patella height was 41.2 mm for left patellae and 40.5 mm for right patellae (t = 1.12, p = 0.27). Similar trends were observed for other parameters, including patella width, thickness, and articular facet dimensions. Conclusion The study found no significant anatomic differences in patellar dimensions between the left and right sides. The slight variations observed are within the range of normal anatomical variability, suggesting that the left and right patellae are largely symmetrical. Recommendations Orthopedic surgeons and rehabilitation specialists should consider the symmetry of patellar dimensions in clinical practice. Future research could explore patellar asymmetries in different populations and their implications for knee joint biomechanics and surgical outcomes.